Effects of Uncertainty, Appraisal of Uncertainty, and Self-Efficacy on the Quality of Life of Elderly Patients with Lung Cancer Receiving Chemotherapy: Based on Mishel’s Theory of Uncertainty - Min-Kyung Hwang; Hee-Kyung Kim; Ki-Hyeong Lee (Medicina, 2023)
Background and Objectives: The purpose of this study is to enhance the quality of life in elderly patients with lung cancer by understanding relations of uncertainty, appraisal of uncertainty, self-efficacy, and quality of life targeting elderly patients with lung cancer receiving anticancer therapy, and also analyzing the factors affecting the quality of life based on Mishel’s theory. Materials and Methods: The subjects were a total of 112 lung cancer patients aged 65 or older receiving anticancer therapy. The data was collected by using self-report questionnaires targeting patients in hemato-oncology at Chungbuk National University Hospital. The data were analyzed using descriptive statistics, a t-test, an analysis of variance, Pearson’s correlational coefficients, and hierarchical regression analysis. Results: In stage 1, anticancer therapy (chemotherapy) (β = −0.34, p < 0.001), economic condition (low) (β = −0.30, p < 0.001), the number of anticancer therapies (three times or more) (β = −0.29, p < 0.001), and education (graduation from high school or higher) (β = 0.18, p = 0.033) were influencing factors (F = 0.52, p < 0.001). In stage 2, self-efficacy (β = 0.41, p < 0.001), appraisal of uncertainty: danger (β = −0.29, p < 0.001), appraisal of uncertainty: opportunity (β = 0.18, p = 0.018), the number of anticancer therapies (three times or more) (β = −0.17, p = 0.006), and anticancer therapy (chemotherapy) (β = −0.14, p = 0.031) were influencing factors, which showed 74.2% explanatory power (F = 26.17, p < 0.001). Conclusions: In order to improve the quality of life of subjects, it would be necessary to develop interventions for raising their self-efficacy by considering their degree of education, economic condition, the types and numbers of anticancer therapies, and understanding of the appraisal of uncertainty about the disease is assessed as an opportunity factor or a danger factor.